Political Power and Cultural Change: Historical Narratives and Social Structures in Comparative Perspective - Muh Irfan Mukhlishin; Aries Purwanto; Chandra Arie Widiyoko; Endang Sriwahyuni (Journal of Humanities Research Sustainability, 2026)
Background. Historical narratives are critical in shaping both political power and social structures within societies. These narratives not only reflect past events but also contribute to the construction of collective identities and the legitimization of political authority. Understanding how these narratives influence cultural change is crucial for examining the interplay between political power and societal transformation across different contexts. Purpose. This study aims to explore the relationship between political power, historical narratives, and cultural change by examining how social structures are depicted and reshaped through historical accounts in various political regimes. The research compares the role of these narratives in societies with different political systems, including monarchies, democracies, and authoritarian states. Method. A comparative historical analysis is employed, focusing on key historical narratives from selected societies. Textual analysis of primary sources, alongside secondary literature, is used to identify the ways in which historical events are framed to reinforce or challenge political power and social hierarchies. Results. The study reveals that historical narratives serve as powerful tools for consolidating political power, often manipulating cultural memory to legitimize dominant social structures. However, these narratives also provide spaces for contestation, allowing alternative perspectives and social movements to challenge established norms. Conclusion. This research concludes that historical narratives are central to the dynamics of political power and cultural change, offering insights into how societies negotiate social structures through the lens of history.